Penggunaan Think-Pair-Share untuk Meningkatkan Keaktifan dan Pemahaman Membaca Siswa dalam Reading Comprehension - Yadhi Nur Amin (Balai Diklat Keagamaan Semarang, 2020)
This study aims to improve the students’ activeness and comprehension in reading comprehension. The subjects are students of class XI MIPA-1 MAN 2 Rembang taught by Think-Pair-Share strategy. The expected output is the increase of students’ activeness and comprehension, so the instrument used is observation sheet to find out the students’ activeness, and a test to determine their comprehension. The method is CAR consisting of four stages (planning, implementation, observation, and reflection). This research was conducted in two cycles. The results showed that Think-Pair-Share strategy could increase the students’ activeness and comprehension. The data analysis of activeness showed an increase from pre-cycle of 39.39% (low), Cycle I 79.29% (fair), to Cycle II 89.90% (high). Furthermore, the result of comprehension showed an increase from pre-cycle 45.45% (low), Cycle I 66.67% (fair), to Cycle II 87.88% (high). Thus, this strategy is considered successful because the final result exceeds the 75% success criteria.